1998
DOI: 10.1093/nar/26.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Genome structure and gene content in protist mitochondrial DNAs

Abstract: Although the collection of completely sequenced mitochondrial genomes is expanding rapidly, only recently has a phylogenetically broad representation of mtDNA sequences from protists (mostly unicellular eukaryotes) become available. This review surveys the 23 complete protist mtDNA sequences that have been determined to date, commenting on such aspects as mitochondrial genome structure, gene content, ribosomal RNA, introns, transfer RNAs and the genetic code and phylogenetic implications. We also illustrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
217
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(229 citation statements)
references
References 96 publications
(112 reference statements)
6
217
1
4
Order By: Relevance
“…Hence, the genes for Calvin cycle enzymes including SBP and FBP were recruited only once in the course of secondary endosymbiosis, then adapted to the complex red plastid, and subsequently spread to unrelated lineages as part of third hand plastids. Tertiary endosymbioses would also explain the otherwise contradictory data of mitochondrial genes and 18S rDNA (Sanchez Puerta et al 2004, Van de Peer andDe Wachter 1997), as well as account for the different types of mitochondria across "chromists" (Gray et al 1998). The location of the complex algal clade in the cytosolic FBP tree ( Fig.…”
Section: Implications For the Evolution Of Complex Algaementioning
confidence: 95%
See 1 more Smart Citation
“…Hence, the genes for Calvin cycle enzymes including SBP and FBP were recruited only once in the course of secondary endosymbiosis, then adapted to the complex red plastid, and subsequently spread to unrelated lineages as part of third hand plastids. Tertiary endosymbioses would also explain the otherwise contradictory data of mitochondrial genes and 18S rDNA (Sanchez Puerta et al 2004, Van de Peer andDe Wachter 1997), as well as account for the different types of mitochondria across "chromists" (Gray et al 1998). The location of the complex algal clade in the cytosolic FBP tree ( Fig.…”
Section: Implications For the Evolution Of Complex Algaementioning
confidence: 95%
“…glyceraldehyde-3-phosphate dehydrogenase (GAPDH), class II fructose-1,6-bisphosphate aldolase (FBA-II), and phosphoribulokinase (PRK) also support the monophyly of "chromalveolate plastids", although none of these nuclear-encoded genes displays the expected red algal affiliation (Harper and Keeling 2003;Patron et al 2004;Petersen et al 2006). Moreover, the monophyly of all "chromalveolate host cells" is at best elusive (Gray et al 1998;Li et al 2006;Sánchez Puerta et al 2004;Van de Peer and De Wachter1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly there is a group of mitochondrial genes which rarely have been transferred to the nucleus and are therefore well suited to test the hypothesis on the evolution of gene length in mitochondria. These genes encode subunits I-III of cytochrome c oxidase (coxI-III) and cytochrome b (cytb), as well as the small (ssu) and large (lsu) subunit rRNAs (Gray et al 1998. It has been suggested that the presence of coxI-III and cytb genes in the mitochondrial genome is essential since their protein products can regulate their expression in response to the redox potential of the mitochondrion (Allen 2003).…”
Section: Introductionmentioning
confidence: 99%
“…M itochondrial genomes exhibit a 20-fold range in protein gene content, from only three in the virtually extinct mtDNA of Plasmodium and other apicomplexans to 61 in Reclinonomas (1,2). However, even Reclinomonas mtDNA encodes but a small fraction of the proteins encoded by the bacterial progenitor of the mitochondrion (3).…”
mentioning
confidence: 99%